2009
DOI: 10.1093/bioinformatics/btp383
|View full text |Cite
|
Sign up to set email alerts
|

Swift: primary data analysis for the Illumina Solexa sequencing platform

Abstract: Motivation: Primary data analysis methods are of critical importance in second generation DNA sequencing. Improved methods have the potential to increase yield and reduce the error rates. Openly documented analysis tools enable the user to understand the primary data, this is important for the optimization and validity of their scientific work.Results: In this article, we describe Swift, a new tool for performing primary data analysis on the Illumina Solexa Sequencing Platform. Swift is the first tool, outside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 13 publications
1
67
0
Order By: Relevance
“…In the present study, we also observed that UMI logic eliminates the so-called optical duplicates (42), that is, cases when a single DNA cluster (raw Illumina instrument signal that is processed into a sequencing read) is misidentified as a group of several identical DNA clusters. Such duplicates could be clearly detected as a peak of read pairs that carry the same UMI with the intercluster distance ,100 pixels (Fig.…”
Section: Revising Umi-based Analysissupporting
confidence: 60%
“…In the present study, we also observed that UMI logic eliminates the so-called optical duplicates (42), that is, cases when a single DNA cluster (raw Illumina instrument signal that is processed into a sequencing read) is misidentified as a group of several identical DNA clusters. Such duplicates could be clearly detected as a peak of read pairs that carry the same UMI with the intercluster distance ,100 pixels (Fig.…”
Section: Revising Umi-based Analysissupporting
confidence: 60%
“…There are two main approaches to addressing this challenge: (1) One approach is to develop improved image analysis and base-calling algorithms. This line of work has been pursued by several researchers in the past, including ourselves (for review, see Erlich et al 2008;Rougemont et al 2008;Kao et al 2009;Kircher et al 2009;Whiteford et al 2009; Kao and Song 2011). Indeed, by using more sophisticated statistical methods, it has been demonstrated that it is possible to deliver significant improvements over the tools developed by the manufacturers of the sequencing platforms.…”
mentioning
confidence: 99%
“…In this case (and in case when heterogeneous data are merged) it is recommended to re-calibrate the data using formula (1) [146,149,150]. There is in-house Sanger Institute recalibration and error analysis implemented [30].…”
Section: Box 10mentioning
confidence: 99%